3D hydrodynamic simulations of C ingestion into a convective O shell. Issue 1 (22nd October 2019) - Andrassy, R; Herwig, F; Woodward, P; Ritter, C
ABSTRACT: Interactions between convective shells in evolved massive stars have been linked to supernova impostors, to the production of the odd-Z elements Cl, K, and Sc, and they might also help generate the large-scale asphericities that are known to facilitate shock revival in supernova explosion models. We investigate the process of ingestion of C-shell material into a convective O-burning shell, including the hydrodynamic feedback from the nuclear burning of the ingested material. Our 3D hydrodynamic simulations span almost 3 dex in the total luminosity L tot . All but one of the simulations reach a quasi-stationary state with the entrainment rate and convective velocity proportional to L tot and $L_tot^{1/3}$, respectively. Carbon burning provides $14\!-\!33{{\ \rm per\ cent}}$ of the total luminosity, depending on the set of reactions considered. Equivalent simulations done on 768 3 and 1152 3 grids are in excellent quantitative agreement. The flow is dominated by a few large-scale convective cells. An instability leading to large-scale oscillations with Mach numbers in excess of 0.2 develops in an experimental run with the energy yield from C burning increased by a factor of 10. This run represents most closely the conditions expected in a violent O–C shell merger, which is a potential production site for odd-Z elements such as K and Sc and which may seed asymmetries in the supernova progenitor. 1D simulations may underestimate the energy generation from the burning of ingested material by as much as a factor 2 owing to their missing the effect of clumpiness of entrained material on the nuclear reaction rate.